Smoker's identity scale: Measuring identity in tobacco dependence and its relationship with confidence in quitting. (7th September 2015) - Dupont, Patrick; Tack, Valentine; Blecha, Lisa; Reynaud, Michel; Benyamina, Amine; Amirouche, Ammar; Aubin, Henri‐Jean
<x xml:space="preserve">Abstract</x> Background and objectives Persistent smoking behaviours are associated with numerous motives, explaining the absence of a single treatment for quitting. One of these motives may include that of identification. The threat of losing their smoker's identity may represent a significant obstacle to lasting abstinence. The objective of this study is to design a specific identity questionnaire and examine correlations between the degree of smoking identity and persistent smoking. Methods Patients attending a smoking cessation seminar completed the Modified Reasons for Smoking Scale, Barriers to smoking cessation checklist and our 6‐item Smoker's Identity Scale (SIS) (n = 170 questionnaires). Results SIS showed good internal consistency, calculated by a Chronbach test (α = .785) with no redundant questions. There was a correlation between strong tobacco dependence (measured by the Fagerström questionnaire) and strong smoking identity (p = .0001). Strong identity was associated with less confidence in quitting at both 1 and 6 months (p = .037 and p = .002, respectively). We showed that identity represents an obstacle to quitting in 32% of our patients and is associated with decreased confidence in quitting. Conclusions and scientific significance Our study shows that measuring identity in smokers who wish to make a quit attempt may help to identify specific obstacles to abstinence. This may also help in elaborating improved quitting strategies and patient management. Further research is necessary to confirm these results. (Am J Addict 2015;XX:XX –XX)